A Unique Aliphatic Tertiary Amine Chromophore: Fluorescence, Polymer Structure, and Application in Cell Imaging - Sun, Miao; Hong, Chun-Yan; Pan, Cai-Yuan (Journal of the American Chemical Society, 2012)
Although photoluminescence of tertiary aliphatic amines has been extensively studied, the usage of this fundamental chromophore as a fluorescent probe for various applications has unfortunately not been realized because their uncommon fluorescence is easily quenched, and strong fluorescence has been observed only in vapor phase. The objective of this study is how to retain the strong fluorescence of tertiary amines in polymers. Tertiary amines as branching units of the hyperbranched poly(amine-ester) (HypET) display relatively strong fluorescence (Φ = 0.11–0.43). The linear polymers with tertiary amines in the backbone or as the side group are only very weakly fluorescent. The tertiary amine of HypET is easily oxidized under ambient conditions, and red-shifting of fluorescence for the oxidized products has been observed. The galactopyranose-modified HypET exhibits low cytotoxicity and bright cell imaging. Thus, this study opens a new route of synthesizing fluorescent materials for cell imaging, biosensing, and drug delivery.